EFFECTS OF NITROGEN STARVATIONS ON CELL GROWTH, PROTEIN AND LIPID AMOUNT OF Chlorella vulgaris - Agirman, Nur; Cetin, A. Kadri (Parlar Scientific Publications (P S P), 2015)
The objective of this study was to examine the effects of the changes in nitrogen amount in the culture medium on the protein and lipid amounts of Chlorella vulgaris. It was observed that nitrogen starvation does not have significant effect on the cell division of Chlorella vulgaris. Protein and lipid values of C. vulgaris were found as 69.20 mu g/ml and 10.5% for control cultures, 56.75 mu g/ml and 12.4 % for 25% nitrogen starvations and 54.35 mu g/ml and 13.6 % for 50% nitrogen starvations. It was also determined that nitrogen deficiency causes lipid accumulation in Chlorella vulgaris and that the lipid amount has increased by about 80 %. The highest lipid content was observed in the maintained culture with 50 % nitrogen starvations. The low nitrogen medium induces higher lipid accumulation. It was concluded that nitrogen stress changes carbon flow from protein synthesis to lipid synthesis thus causing lipid accumulation in Chlorella vulgaris.
Keywords: Chlorella vulgaris; Nitrogen Starvations; Lipid accumulation; Protein amount